Dopant‐Induced Giant Photoluminescence of Monolayer MoS2 by Chemical Vapor Transport (Adv. Mater. Interfaces 25/2022). Issue 25 (2nd September 2022) - Ma, Zhao; Ren, Caixia; Wu, Yu; Qiu, Hailong; Liu, Hongjun; Hu, Zhanggui; Wu, Yicheng
Abstract : Photoluminescence of Monolayer MoS2 The Ti‐doped MoS2 monolayers with ultra‐high photoluminescence (PL) intensity are successfully synthesized through chemical vapor transport as reported in article number 2200431 by Zhao Ma, Hailong Qiu, and co‐workers. The PL intensity from the Ti‐doped MoS2 is 85‐fold stronger than that from the pristine MoS2 . The giant PL enhancement is attributed to dopant‐induced O‐Ti‐S units and improved interaction between the monolayer and the mica substrate, increasing the photoluminescence quantum yield and suppressing the non‐radiative recombination.